Pengelolaan keuangan desa berbasis aplikasi siskeudes dalam perspektif Technology Acceptance Model (TAM) pada Desa di Kecamatan Luahagundre Maniamolo - Nestan Theresia Natalia; Arthur Simanjuntak; Ivo Maelina Silitonga (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2026)
This study aims to analyze the effect of Perceived Usefulness and Perceived Ease of Use on village financial management through the Village Financial System (Siskeudes) application within the framework of the Technology Acceptance Model (TAM). This research applies a quantitative approach using primary data collected through questionnaires distributed to village officials directly involved in managing village finances using the Siskeudes application. The population consists of all village officials in Luahagundre Maniamolo District, with a sample of 40 respondents selected using purposive sampling. The data analysis techniques include descriptive statistics, validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing using SPSS version 25. The results indicate that Perceived Usefulness and Perceived Ease of Use have a positive and significant effect on village financial management, both partially and simultaneously. These findings imply that higher levels of perceived usefulness and ease of use of the Siskeudes application lead to more effective, transparent, and accountable village financial management.